Effect of Ar ion irradiation on the room temperature ferromagnetism of undoped and Cu-doped rutile TiO_2 single crystals - 许楠楠 李公平 林俏露 刘欢 包良满 (中国物理B：英文版, 2016)
Remarkable room-temperature ferromagnetism was observed both in undoped and Cu-doped rutile TiO2 single crystals（SCs）.To tune their magnetism,Ar ion irradiation was quantitatively performed on the two crystals in which the saturation magnetizations for the samples were enhanced distinctively.The post-irradiation led to a spongelike layer in the near surface of the Cu-doped TiO2.Meanwhile,a new CuO-like species present in the sample was found to be dissolved after the post-irradiation.Analyzing the magnetization data unambiguously reveals that the experimentally observed ferromagnetism is related to the intrinsic defects rather than the exotic Cu ions,while these ions are directly involved in boosting the absorption in the visible region.